Direct and continuous hydrothermal flow synthesis of thermochromic phase pure monoclinic VO2 nanoparticles. Issue 43 (30th October 2018) - Malarde, Delphine; Johnson, Ian D.; Godfrey, Ian J.; Powell, Michael J.; Cibin, Giannantonio; Quesada-Cabrera, Raul; Darr, Jawwad A.; Carmalt, Claire J.; Sankar, Gopinathan; Parkin, Ivan P.; Palgrave, Robert G.
Abstract : The first direct synthesis of pure thermochromic VO2 (M) nanoparticles with particle sizes below 50 nm by continuous hydrothermal flow synthesis (CHFS). Abstract : Monoclinic vanadium(iv ) oxide [VO2 (M)] is a widely studied material due to its thermochromic properties and its potential use in energy-efficient glazing applications. VO2 (M) nanoparticles can be a great advantage for energy-efficient glazing as below 50 nm the nanoparticles poorly interact with visible wavelengths – resulting in an increase in visible light transmittance whilst maintaining the thermochromic response of the material. The direct synthesis of VO2 (M) nanoparticles with effective thermochromic properties will be a step forward towards industrial applications of this material. Unfortunately, many of the synthesis processes reported so far involve multiple steps, including post-treatment, and the synthesis is not always reproducible. In this study, we present the first direct synthesis of pure monoclinic VO2 nanoparticles by continuous hydrothermal flow synthesis (CHFS). TEM images showed that nanoparticles in the size range of 30–40 nm were produced. The VO2 (M) nanoparticles also showed good thermochromic properties with a solar modulation (Δ T sol ) of 3.8%, as established by UV/Vis spectroscopy. A range of analytical methods was used to characterise the materials, including X-ray absorption spectroscopy (XANES and EXAFS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). The influence of niobium (Nb) doping on the physical and thermochromic properties of the VO2 nanoparticles was also explored. Previous work has shown a sharp metal-to-semiconductor transition of VO2 upon incorporation of a Nb dopant. The results of the current work suggested that these changes are likely due to changes on the local structure of the oxide.